Адаптивні особливості Південнобузьких ендемів Dianthus hypanicus Andrz. та Moehringia hypanica Grynj et Klok - Соломаха, В.А.; Драбинюк, Г.В.; Вініченко, Т.С; Мойсієнко, І.І.; Деркач, О.М. (Український фітоценологічний збірник, 2006)
Выявлены эколого-ценотические и адаптационные особенности южнобугских эндемов Dianthus hypanicus и Moehringia hypanicа, приспособленных к произрастанию на гранитных обнажениях и скалах. Предлагается синтаксономия растительных сообществ Moehringia hypanicа, представленная асоциацией Moehringietum hypanicae ass. nova, D.c. Dianthus hypanicus+Moehringia hypanica [Cl. Asplenietea trichomanis], D.c. Cystopteris fragilis+Moehringia hypanica [Cl. Asplenietea trichomanis] класcа Asplenietea trichomanis Br.-Bl., in Meyer et Br.-Bl. 1934 Oberdorfer 1977 и D. c. Aurinia saxatilis+Moehringia hypanica [All. Alysso—Sedion] класса Sedo-Sclerantethea Br.-Bl. 1955 em Moraveс 1967. Dianthus hypanicus представлен ассоциацией Sedo acri-Dianthetum hypanicii ass. Nova и D. c. Sempervivum ruthenicum+Dianthus hypanicus [All. Alysso—Sedion], D. c. Aurinia saxatilis+Moehringia hypanica [All. Alysso—Sedion] класса SedoSclerantethea Br.-Bl. 1955 em Moraveс 1967 и D. с. Allium podolicum+Dianthus hypanicus [All. Festucion valesiacae] класса Festuco-Brometea Br.-Bl. et Tuxen ex Braun-Blanquet 1949. The ecology-cenotic and adaptative peculiarities of the South-Bug endemics Dianthus hypanicus and Moehringia hypanicà, adopted to the growth on granite outcrops and rocks, have been found out. The syntaxonomy of plant communities of Moehringia hypanica, which is represented with the association of Moehringietum hypanicae ass. nova, has been discovered. D.c. Dianthus hypanicus+Moehringia hypanica [Cl. Asplenietea trichomanis], D.c. Cystopteris fragilis+Moehringia hypanica [Cl. Asplenietea trichomanis] of the class Asplenietea trichomanis Br.-Bl., in Meyer et Br.-Bl. 1934 Oberdorfer 1977 and D. c. Aurinia saxatilis+Moehringia hypanica [All. Alysso—Sedion] of the class Sedo-Sclerantethea Br.-Bl. 1955 em Moraveñ 1967. Dianthus hypanicus is represented with the association of Sedo acri-Dianthetum hypanicii ass. Nova and D.c. Sempervivum ruthenicum+Dianthus hypanicus [All. Alysso—Sedion], D. c. Aurinia saxatilis+Moehringia hypanica [All. Alysso—Sedion] of the class Sedo-Sclerantethea Br.-Bl. 1955 em Moraveñ 1967 and D.c. Allium podolicum+Dianthus hypanicus [All. Festucion valesiacae] of the class Festuco-Brometea Br.-Bl. et Tuxen ex Braun-Blanquet 1949.